1983
DOI: 10.1093/bja/55.8.761
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Lorazepam: A Better Premedication?

Abstract: The efficacy of a sublingual preparation of lorazepam was compared with an i.m. injection of lorazepam as premedication for 150 patients undergoing minor gynaecological surgery. Anxiety, arousability and recall of auditory, visual and tactile stimuli were used as measurements of the degree and rate of onset of the effects. Anxiety scores decreased in both groups after medication. Patients who received the drug sublingually showed less recall, an earlier onset of sedation, more drowsiness and a longer recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Respiratory depression was observed in 3 patients (1 midazolam, 2 diazepam) in a study of 85 patients by Magni et al 14 In another study prolonged sedation was observed in the sublingual group compared to intramuscular group of lorazepam. 15 Midazolam was found to be preferable to diazepam and lorazepam because shorter duration of action provided lesser chances of delayed recovery or prolonged sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory depression was observed in 3 patients (1 midazolam, 2 diazepam) in a study of 85 patients by Magni et al 14 In another study prolonged sedation was observed in the sublingual group compared to intramuscular group of lorazepam. 15 Midazolam was found to be preferable to diazepam and lorazepam because shorter duration of action provided lesser chances of delayed recovery or prolonged sedation.…”
Section: Discussionmentioning
confidence: 99%
“…or s.l., 1 -2 h preoperatively) is also an effective choice for sedation or anxiolysis. However, the prolonged duration of action may prolong recovery time after shorter cases [261]. Midazolam (5 -7.5 mg i.m., 30 min preoperatively, or 2 mg i.v.…”
Section: Preoperative Preparationmentioning
confidence: 99%